(untitled) (Archives of Clinical Psychiatry, 2007)
BACKGROUND: The concept of remission is well established in some psychiatric disorders such as depression, but only recently it has been proposed for schizophrenia. OBJECTIVE: The aim of the present paper is to review the new proposed criteria for remission in schizophrenia. METHOD: PubMed search. RESULTS: The concept of remission, response, stability and recover are extensively discussed in the present article, as well as items of the scales used in the definition. CONCLUSION: The concept of remission is characterized by the presence in the last 6 months of symptoms with a maximum threshold severity level (Panss level 3) but which allows a certain degree of social functioning. The dimensions of the concept and respective psychopathological symptoms are: Positive: delusions, hallucinations and unusual thought content. Disorganization: conceptual disorganization and mannerisms and posturing; Negative: blunted affect, passive/apathetic social withdrawal and lack of spontaneity and flow of conversation.